Climate drove gradual rainforest transitions in Wallacea (Sulawesi, Indonesia) during the last glacial-interglacial transition (24,000 – 9,000 years BP) - Adam J. Benfield; Sarah J. Ivory; Rebecca Hamilton; Janelle Stevenson; Meredith C. Parish; Satria Bijaksana; Hendrik Vogel; James M. Russell (Quaternary Science Reviews, 2026)

Smooth Gradients or Defined Fronts: Characterizing Within-Marsh Spatial Variability of CO2 Fluxes - Lena K. Champlin; Emily Wilson; Kenneth B. Raposa; Jason S. Goldstein; Ashley Hamilton; Jason S. Krumholz; Christopher R. Peter; Megan C. Tyrrell; Jamie M. P. Vaudrey; Robinson W. Fulweiler (Estuaries and Coasts, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Petrogenesis and Provenance of Unique Amphibole-Bearing Carbonaceous Chondrite Almahata Sitta 202: Further Evidence for a Ceres-Sized, Water-Rich Parent Body - Cyrena A. Goodrich; Victoria E. Hamilton; Michael E. Zolensky; Noriko Kita; Issaku Kohl; Lauren Tafla; Robert J. Macke; Takahiro Hiroi; Yoko Kebukawa; Wayne Buckley; Jacob B. Setera; Justin I. Simon; et al. (Geochimica et Cosmochimica Acta, 2026)

Exploring trait- and state-based dietary restraint using ecological momentary assessment - Rebecca L. Elsworth; Elanor C. Hinton; Julian P. Hamilton-Shield; Natalia S. Lawrence; Jeffrey M. Brunstrom (Appetite, 2026)

Impact of diagenesis and acidic alteration on microbial fabrics and trace element distributions in fossilised siliceous hot spring deposits - Barbara J. Lyon; Michael C. Rowe; Andrew Langendam; Kathleen A. Campbell; Diego M. Guido; Ayrton R. Hamilton; Ema E. Nersezova; Amanda Galar; Dominique A. Stallard (Geochimica et Cosmochimica Acta, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Detection of Cryptosporidium spp. and Giardia duodenalis DNA in wild deer in Scotland - Paul M. Bartley; Clare M. Hamilton; Jackie Thomson; Ross Bacchetti; Mairi C. Mitchell; Tom N. McNeilly; Renata Pimentel Bandeira de Melo; Adam D. Hayward; Frank Katzer; Beth Wells (Veterinary Parasitology, 2025)

Characterization of a Peptidoglycan-Degrading Protein: Biochemical and Antimicrobial Characteristics, Antibiotic Synergism, and Delivery System Innovation - Viviane C. Oliveira; Nathália G. Rosa-Garzon; Amanda C.S.D. Rocha; Rachel M. Monteiro; Yasmim G. Gonçalves; Marcelo Kravicz; Maria A. Juliano; Luiz Juliano; Priscyla D. Marcato; Claudia H. Silva-Lovato; Hamilton Cabral; Evandro Watanabe (Probiotics and Antimicrobial Proteins, 2025)

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Supramolecular environment and androgen receptor binding of taraxerol: from molecular structure to potential bioactivity function - Lara L. G. C. Rodrigues; Vitor S. Duarte; Antônio S. N. Aguiar; Vitória A. M. Silva; Hamilton B. Napolitano; Leonardo L. Borges (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Improved estimation of aquaculture associated European introgression in a captive breeding program for endangered Atlantic salmon - Melissa K. Holborn; Tony Kess; Cameron M. Nugent; Nathalie N. Brodeur; Joke Adesola; Evan Cronmiller; Lorraine C. Hamilton; Ross A. Jones; Beth L. Lenentine; Anna MacDonnell; Meghan McBride; Amber Messmer; et al. (Conservation Genetics, 2025)
The rapid, range-wide decline in Atlantic salmon, Salmo salar , populations is well documented and has led to establishment of captive rearing and breeding programs in order to preserve populations. However, recovery potential may be limited by the inclusion of non-local genotypes, which can be both difficult to detect and quantify. In the genetically unique Inner Bay of Fundy population located in Canada, three Live Gene Bank programs have been established to aid recovery of this endangered conservation unit. Evidence of aquaculture associated non-local (i.e., European) introgression had previously been detected using small panels of microsatellite markers with limited power. Here we show how advances in sequencing and machine learning technologies can support a conservation program. We used machine learning and a corresponding panel of 301 SNPs to estimate individual-level proportions of European ancestry. To assess the degree of introgression in each program and to assess changes over time, fish were randomly selected across several program generations. Estimates were validated by genotyping a subset of individuals on a 220 K SNP array and using established admixture methods. Of the 1741 fish analyzed, only 48 were found to have European ancestry greater than the detection threshold. We found the amount of European ancestry was previously overestimated, and that very few wild-collected founder individuals had large proportions of European ancestry. Moreover, because European ancestry was introduced to Bay of Fundy populations via introgression from aquaculture escapees, these values represent the minimum amount of aquaculture introgression in these captive populations.

Testing a rapid assessment approach for estimating ecosystem service capacity in urban green alleys - Marie C. Dade; Isabella C. Richmond; Jesse T. Rieb; Erin T.H. Crockett; Kayleigh Hutt-Taylor; Serena Sinno; Karina Benessaiah; Catherine Destrempes; Jacqueline Hamilton; Fatemeh Izadi; L. Emily Kroft; Lingshan Li; et al. (Urban Forestry & Urban Greening, 2024)

Trace metal and organic biosignatures in digitate stromatolites from terrestrial siliceous hot spring deposits: Implications for the exploration of martian life - Ema E. Nersezova; Michael C. Rowe; Kathleen A. Campbell; Andrew Langendam; Cherie Tollemache; Barbara Lyon; Amanda Galar; Diego M. Guido; Bronwyn L. Teece; Trinity L. Hamilton (Chemical Geology, 2024)

Assessing effects of a novel weight-management product on appetite - Rebecca L. Elsworth; Elanor C. Hinton; Julian P. Hamilton-Shield; James Byrne; Camilla Easter; Hutan Ashrafian; Jeffrey M. Brunstrom (Appetite, 2024)

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

Modeling coupled dynamics of an empirical predator-prey system to predict top predator recovery - Samantha N.M. Hamilton; M. Tim Tinker; Joseph Jackson; Joseph A. Tomoleoni; Michael C. Kenner; Julie L. Yee; Tom W. Bell; Max C.N. Castorani; Benjamin H. Becker; Brent B. Hughes (Biological Conservation, 2024)

Development of Momentary Appetite Capture (MAC): A versatile tool for monitoring appetite over long periods - Rebecca L. Elsworth; Elanor C. Hinton; Annika N. Flynn; Lucy H. Merrell; Julian P. Hamilton-Shield; Natalia S. Lawrence; Jeffrey M. Brunstrom (Appetite, 2024)

Genetic sex determination improves Canadian Atlantic salmon ( Salmo salar ) population assessments - Martha J. Robertson; Sarah J. Lehnert; Nicholas I. Kelly; Lorraine C. Hamilton; Ross A. Jones; Alex L. Levy; Rebecca Poole; Chantelle M. Burke; Steven J. Duffy; Amber Messmer; Ian R. Bradbury (Fisheries Management and Ecology, 2024)
Estimating egg deposition for Atlantic salmon population assessments is made difficult by their lack of sexual dimorphism prior to the autumn spawning season. We quantified the effect of sex misclassification from subjective examination of external morphology on egg deposition estimates in four Atlantic salmon populations across multiple years. Sex classification of Canadian salmon using the genetic sex marker ( sd Y) was accurate (>97%), whereas sex classification based on subjective examination of external morphology was inaccurate, with misclassification rates dependent on sea age, life history, and sampling season. Sex misclassification led to annual egg deposition estimates that ranged from −36% to +56%. We found that sex could not be discriminated based on measures of external morphology.

Suspected anthropogenic microparticle ingestion by Icelandic capelin - Caitlin Brawn; Bonnie M. Hamilton; Matthew S. Savoca; Birkir Bardarson; Jesse C. Vermaire; Jennifer Provencher (Marine Pollution Bulletin, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

A ring trial to harmonize Toxoplasma gondii microsatellite typing: comparative analysis of results and recommendations for optimization - M. Joeres; G. Cardron; K. Passebosc-Faure; N. Plault; M. Fernández-Escobar; C. M. Hamilton; L. O’Brien-Anderson; R. Calero-Bernal; L. Galal; C. Luttermann; P. Maksimov; F. J. Conraths; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
A ring trial among five European laboratories was organized to reach consistency in microsatellite (MS) typing of the zoonotic parasite Toxoplasma gondii . Three sample sets were circulated and analyzed by each laboratory following a previously published method that is based on fragment length polymorphism of 15 MS markers. The first sample set compared typing results in general and focused on effects of DNA concentration; the second sample set focused on the polymorphic fingerprinting markers that can differentiate T. gondii strains within the same archetypal lineage; and the third set focused on non-archetypal genotypes. Methodological variations between laboratories, including the software programs used to determine MS fragment length, were collated using a questionnaire. Overall, lineage-level typing results reached a high level of agreement, especially in samples with the highest DNA concentrations. However, laboratory-specific differences were observed for particular markers. Major median differences in fragment length, of up to 6 base pairs, were related to the fluorophore used to label fragment-specific primers. In addition, primer pairs with identical sequences obtained from different suppliers resulted in fragments of differing length. Furthermore, differences in the way the sequencing profiles were assessed and interpreted may have led to deviating results in fragment length determination. Harmonization of MS typing, for example, by using the same fluorophores or by numerical adjustments applied to the fragment-lengths determined, could improve the uniformity of the results across laboratories. This is the first interlaboratory comparison, providing guidelines (added as a supplement) for the optimization of this technique.

Planktic foraminifera iodine/calcium ratios from plankton tows - Helge A. Winkelbauer; Babette A. A. Hoogakker; Rosie J. Chance; Catherine V. Davis; Christopher J. Anthony; Juliane Bischoff; Lucy J. Carpenter; Simon R. N. Chenery; Elliott M. Hamilton; Philip Holdship; Victoria L. Peck; Alex J. Poulton; et al. (Frontiers in Marine Science, 2023)
Planktic foraminifera test iodine to calcium ratios represent an emerging proxy method to assess subsurface seawater oxygenation states. Several core-top studies show lower planktic foraminifera I/Ca in locations with oxygen depleted subsurface waters compared to well oxygenated environments. The reasoning behind this trend is that only the oxidized species of iodine, iodate, is incorporated in foraminiferal calcite. The I/Ca of foraminiferal calcite is thought to reflect iodate contents in seawater. To test this hypothesis, we compare planktic foraminifera I/Ca ratios, obtained from plankton tows, with published and new seawater iodate concentrations from 1) the Eastern North Pacific with extensive oxygen depletion, 2) the Benguela Current System with moderately depleted oxygen concentrations, and 3) the well oxygenated North and South Atlantic. We find the lowest I/Ca ratios (0.07 µmol/mol) in planktic foraminifera retrieved from the Eastern North Pacific, and higher values for samples (up to 0.72 µmol/mol) obtained from the Benguela Current System and North and South Atlantic. The I/Ca ratios of plankton tow foraminifera from environments with well oxygenated subsurface waters, however, are an order of magnitude lower compared to core-tops from similarly well-oxygenated regions. This would suggest that planktic foraminifera gain iodine post-mortem, either when sinking through the water column, or during burial.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Assessment of bioaccessibility and health risk of mercury within soil of artisanal gold mine sites, Niger, North-central part of Nigeria - Abiodun M. Odukoya; Bernard Uruowhe; Michael J. Watts; Elliott M. Hamilton; Andrew L. Marriott; Babajide Alo; Nnamdi C. Anene (Environmental Geochemistry and Health, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The Society for Environmental Geochemistry and Health (SEGH): building for the future of early career researchers - O. S. Humphrey; D. R. S. Middleton; S. Ahmad; T. Cocerva; S. M. Dowell; R. Garza-Galndo; E. M. Hamilton; N. Kafwamfwa; B. Kaninga; P. Kourgia; I. S. Ligowe; H. A. MacLeod; et al. (Environmental Geochemistry and Health, 2021)

Sex differences in changes of protein synthesis with rapamycin treatment are minimized when metformin is added to rapamycin - Christopher A. Wolff; Marcus M. Lawrence; Hunter Porter; Qian Zhang; Justin J. Reid; Jaime L. Laurin; Robert V. Musci; Melissa A. Linden; Frederick F. Peelor; Jonathan D. Wren; Joseph S. Creery; Kyle J. Cutler; et al. (GeroScience, 2021)

Alternative Biogeochemical States of River Pools Mediated by Hippo Use and Flow Variability - Christopher L. Dutton; Amanda L. Subalusky; Stephen K. Hamilton; Ella C. Bayer; Laban Njoroge; Emma J. Rosi; David M. Post (Ecosystems, 2021)

The effectiveness of flower strips and hedgerows on pest control, pollination services and crop yield: a quantitative synthesis - Matthias Albrecht; David Kleijn; Neal M. Williams; Matthias Tschumi; Brett R. Blaauw; Riccardo Bommarco; Alistair J. Campbell; Matteo Dainese; Francis A. Drummond; Martin H. Entling; Dominik Ganser; G. Arjen de Groot; et al. (Ecology Letters, 2020)
Floral plantings are promoted to foster ecological intensification of agriculture through provisioning of ecosystem services. However, a comprehensive assessment of the effectiveness of different floral plantings, their characteristics and consequences for crop yield is lacking. Here we quantified the impacts of flower strips and hedgerows on pest control (18 studies) and pollination services (17 studies) in adjacent crops in North America, Europe and New Zealand. Flower strips, but not hedgerows, enhanced pest control services in adjacent fields by 16% on average. However, effects on crop pollination and yield were more variable. Our synthesis identifies several important drivers of variability in effectiveness of plantings: pollination services declined exponentially with distance from plantings, and perennial and older flower strips with higher flowering plant diversity enhanced pollination more effectively. These findings provide promising pathways to optimise floral plantings to more effectively contribute to ecosystem service delivery and ecological intensification of agriculture in the future.

Are anglers exposed to Escherichia coli from an agriculturally impacted river? - Bonnie M. Hamilton; Amanda D. Harwood; Hunter R. Wilson; Timothy P. Keeton; Murray C. Borrello (Environmental Monitoring and Assessment, 2020)

Feral cat eradication on Dirk Hartog Island, Western Australia - D. Algar; M. Johnston; C. Tiller; M. Onus; J. Fletcher; G. Desmond; N. Hamilton; P. Speldewinde (Biological Invasions, 2020)

Limitations of trait‐based approaches for stressor assessment: The case of freshwater invertebrates and climate drivers - Anna T. Hamilton; Ralf B. Schäfer; Matthew I. Pyne; Bruce Chessman; Karan Kakouei; Kate S. Boersma; Piet F. M. Verdonschot; Ralf C. M. Verdonschot; Meryl Mims; Kieran Khamis; Britta Bierwagen; Jen Stamp (Global Change Biology, 2020)
The appeal of trait‐based approaches for assessing environmental vulnerabilities arises from the potential insight they provide into the mechanisms underlying the changes in populations and community structure. Traits can provide ecologically based explanations for observed responses to environmental changes, along with predictive power gained by developing relationships between traits and environmental variables. Despite these potential benefits, questions remain regarding the utility and limitations of these approaches, which we explore focusing on the following questions: (a) How reliable are predictions of biotic responses to changing conditions based on single trait–environment relationships? (b) What factors constrain detection of single trait–environment relationships, and how can they be addressed? (c) Can we use information on meta‐community processes to reveal conditions when assumptions underlying trait‐based studies are not met? We address these questions by reviewing published literature on aquatic invertebrate communities from stream ecosystems. Our findings help to define factors that influence the successful application of trait‐based approaches in addressing the complex, multifaceted effects of changing climate conditions on hydrologic and thermal regimes in stream ecosystems. Key conclusions are that observed relationships between traits and environmental stressors are often inconsistent with predefined hypotheses derived from current trait‐based thinking, particularly related to single trait–environment relationships. Factors that can influence findings of trait‐based assessments include intercorrelations of among traits and among environmental variables, spatial scale, strength of biotic interactions, intensity of habitat disturbance, degree of abiotic stress, and methods of trait characterization. Several recommendations are made for practice and further study to address these concerns, including using phylogenetic relatedness to address intercorrelation. With proper consideration of these issues, trait‐based assessment of organismal vulnerability to environmental changes can become a useful tool to conserve threatened populations into the future.

Quantitative trait loci and differential gene expression analyses reveal the genetic basis for negatively associated β-carotene and starch content in hexaploid sweetpotato [Ipomoea batatas (L.) Lam.] - Dorcus C. Gemenet; Guilherme da Silva Pereira; Bert De Boeck; Joshua C. Wood; Marcelo Mollinari; Bode A. Olukolu; Federico Diaz; Veronica Mosquera; Reuben T. Ssali; Maria David; Mercy N. Kitavi; Gabriela Burgos; et al. (Theoretical and Applied Genetics, 2020)
Key message β-Carotene content in sweetpotato is associated with the Orange and phytoene synthase genes; due to physical linkage of phytoene synthase with sucrose synthase , β-carotene and starch content are negatively correlated. Abstract In populations depending on sweetpotato for food security, starch is an important source of calories, while β-carotene is an important source of provitamin A. The negative association between the two traits contributes to the low nutritional quality of sweetpotato consumed, especially in sub-Saharan Africa. Using a biparental mapping population of 315 F 1 progeny generated from a cross between an orange-fleshed and a non-orange-fleshed sweetpotato variety, we identified two major quantitative trait loci (QTL) on linkage group (LG) three (LG3) and twelve (LG12) affecting starch, β-carotene, and their correlated traits, dry matter and flesh color. Analysis of parental haplotypes indicated that these two regions acted pleiotropically to reduce starch content and increase β-carotene in genotypes carrying the orange-fleshed parental haplotype at the LG3 locus. Phytoene synthase and sucrose synthase, the rate-limiting and linked genes located within the QTL on LG3 involved in the carotenoid and starch biosynthesis, respectively, were differentially expressed in Beauregard versus Tanzania storage roots. The Orange gene, the molecular switch for chromoplast biogenesis, located within the QTL on LG12 while not differentially expressed was expressed in developing roots of the parental genotypes. We conclude that these two QTL regions act together in a cis and trans manner to inhibit starch biosynthesis in amyloplasts and enhance chromoplast biogenesis, carotenoid biosynthesis, and accumulation in orange-fleshed sweetpotato. Understanding the genetic basis of this negative association between starch and β-carotene will inform future sweetpotato breeding strategies targeting sweetpotato for food and nutritional security.

Prevalence and Genetic Diversity of Toxoplasma gondii in Free-Ranging Chickens from the Caribbean - C. M. Hamilton; R. Robins; R. Thomas; C. Oura; S. Oliveira; I. Villena; E. A. Innes; F. Katzer; P. J. Kelly (Acta Parasitologica, 2019)

Different reactivity to glutathione but similar tumor cell toxicity of chalcones and their quinolinone analogues - Giulio D. C. d’Oliveira; Jean M. F. Custodio; Andrea F. Moura; Hamilton B. Napolitano; Caridad N. Pérez; Manoel O. Moraes; László Prókai; Pál Perjési (Medicinal Chemistry Research, 2019)

Seasonal and Long-Term Dynamics in Stream Water Sodium Chloride Concentrations and the Effectiveness of Road Salt Best Management Practices - Victoria R. Kelly; Stuart E. Findlay; Stephen K. Hamilton; Gary M. Lovett; Kathleen C. Weathers (Water, Air, & Soil Pollution, 2019)

Potential for offsetting diamond mine carbon emissions through mineral carbonation of processed kimberlite: an assessment of De Beers mine sites in South Africa and Canada - Evelyn M. Mervine; Sasha Wilson; Ian M. Power; Gregory M. Dipple; Connor C. Turvey; Jessica L. Hamilton; Sterling Vanderzee; Mati Raudsepp; Colette Southam; Juerg M. Matter; Peter B. Kelemen; Johann Stiefenhofer; et al. (Mineralogy and Petrology, 2018)

Resistance training in young men induces muscle transcriptome-wide changes associated with muscle structure and metabolism refining the response to exercise-induced stress - Felipe Damas; Carlos Ugrinowitsch; Cleiton A. Libardi; Paulo R. Jannig; Amy J. Hector; Chris McGlory; Manoel E. Lixandrão; Felipe C. Vechin; Horacio Montenegro; Valmor Tricoli; Hamilton Roschel; Stuart M. Phillips (European Journal of Applied Physiology, 2018)

Constructed treatment wetlands provide habitat for zooplankton communities in agricultural peat lake catchments - Rebecca S. Eivers; Ian C. Duggan; David P. Hamilton; John M. Quinn (Wetlands, 2018)

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

A Qualitative Exploration of Latinos’ Perceptions About Skin Cancer: the Role of Gender and Linguistic Acculturation - Vivian M. Rodríguez; Elyse Shuk; Guedy Arniella; C. Javier González; Francesca Gany; Jada G. Hamilton; Geoffrey S. Gold; Jennifer L. Hay (Journal of Cancer Education, 2017)

Elemental composition of Malawian rice - Edward J. M. Joy; E. Louise Ander; Martin R. Broadley; Scott D. Young; Allan D. C. Chilimba; Elliott M. Hamilton; Michael J. Watts (Environmental Geochemistry and Health, 2017)

Messages of Hope: Helping Family Members to Overcome Fears and Fatalistic Attitudes Toward Cancer - Jill B. Hamilton; Valarie C. Worthy; Angelo D. Moore; Nakia C. Best; Jennifer M. Stewart; Mi-Kyung Song (Journal of Cancer Education, 2017)

Growing older with health and vitality: a nexus of physical activity, exercise and nutrition - Oliver C. Witard; Chris McGlory; D. Lee Hamilton; Stuart M. Phillips (Biogerontology, 2016)

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)

The influence of status and the social environment on energy stores in a social fish - J. K. Hellmann; I. Y. Ligocki; C. M. O'Connor; A. R. Reddon; T. M. Farmer; S. E. Marsh‐Rollo; S. Balshine; I. M. Hamilton (Journal of Fish Biology, 2016)
This study explores how muscle and liver energy stores are linked with social status and the social environment in Neolamprologus pulcher , a cooperatively breeding fish that lives in colonies comprised of up to 200 distinct social groups. Subordinate muscle energy stores were positively correlated with the number of neighbouring social groups in the colony, but this pattern was not observed in dominant N. pulcher . Furthermore, liver energy stores were smaller in dominants living at the edge of the colony compared with those living in the colony centre, with no differences among subordinates in liver energy stores. Subordinate N. pulcher may build up large energy stores in the muscles to fuel rapid growth after dispersal, which could occur more frequently in high‐density environments. Dominant N. pulcher may use the more easily mobilized energy stores in the liver to fuel daily activities, which could be more energetically demanding on the edge of the colony as a result of the increased predation defence needed on the edge. Overall, this study demonstrates that both subordinate and dominant physiology in N. pulcher varies with characteristics of the social environment. Furthermore, dominant and subordinate energy storage strategies appear to differ due to status‐dependent variation in daily activities and variation in the need to prepare for future reproductive or dispersal opportunities.

An inability to distinguish edematous swelling from true hypertrophy still prevents a completely accurate interpretation of the time course of muscle hypertrophy - Felipe Damas; Stuart M. Phillips; Manoel E. Lixandrão; Felipe C. Vechin; Cleiton A. Libardi; Hamilton Roschel; Valmor Tricoli; Carlos Ugrinowitsch (European Journal of Applied Physiology, 2016)

Early resistance training-induced increases in muscle cross-sectional area are concomitant with edema-induced muscle swelling - Felipe Damas; Stuart M. Phillips; Manoel E. Lixandrão; Felipe C. Vechin; Cleiton A. Libardi; Hamilton Roschel; Valmor Tricoli; Carlos Ugrinowitsch (European Journal of Applied Physiology, 2016)

The effect of long-term regional pumping on hydrochemistry and dissolved gas content in an undeveloped shale-gas-bearing aquifer in southwestern Ontario, Canada - Stewart M. Hamilton; Stephen E. Grasby; Jennifer C. McIntosh; Stephen G. Osborn (Hydrogeology Journal, 2015)

Organic matter stocks increase with degree of invasion in temperate inland wetlands - J. P. Martina; S. K. Hamilton; M. R. Turetsky; C. J. Phillippo (Plant and Soil, 2014)

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

The diet of M yotis lucifugus across C anada: assessing foraging quality and diet variability - Elizabeth L. Clare; William O. C. Symondson; Hugh Broders; François Fabianek; Erin E. Fraser; Alistair MacKenzie; Andrew Boughen; Rachel Hamilton; Craig K. R. Willis; Felix Martinez‐Nuñez; Allyson K. Menzies; Kaleigh J. O. Norquay; et al. (Molecular Ecology, 2014)
Variation in prey resources influences the diet and behaviour of predators. When prey become limiting, predators may travel farther to find preferred food or adjust to existing local resources. When predators are habitat limited, local resource abundance impacts foraging success. We analysed the diet of Myotis lucifugus (little brown bats) from Nova Scotia (eastern Canada) to the Northwest Territories (north‐western Canada). This distribution includes extremes of season length and temperature and encompasses colonies on rural monoculture farms, and in urban and unmodified areas. We recognized nearly 600 distinct species of prey, of which ≈30% could be identified using reference sequence libraries. We found a higher than expected use of lepidopterans, which comprised a range of dietary richness from ≈35% early in the summer to ≈55% by late summer. Diptera were the second largest prey group consumed, representing ≈45% of dietary diversity early in the summer. We observed extreme local dietary variability and variation among seasons and years. Based on the species of insects that were consumed, we observed that two locations support prey species with extremely low pollution and acidification tolerances, suggesting that these are areas without environmental contamination. We conclude that there is significant local population variability in little brown bat diet that is likely driven by seasonal and geographical changes in insect diversity, and that this prey may be a good indicator of environment quality.

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

A framework for testing the ability of models to project climate change and its impacts - J. C. Refsgaard; H. Madsen; V. Andréassian; K. Arnbjerg-Nielsen; T. A. Davidson; M. Drews; D. P. Hamilton; E. Jeppesen; E. Kjellström; J. E. Olesen; T. O. Sonnenborg; D. Trolle; et al. (Climatic Change, 2014)

Tracing the origin of US brown marmorated stink bugs, Halyomorpha halys - Jiawu Xu; Dina M. Fonseca; George C. Hamilton; Kim A. Hoelmer; Anne L. Nielsen (Biological Invasions, 2014)

Feasibility and potential role of ferumoxytol-enhanced neuroimaging in HIV-associated neurocognitive disorder - Beau K. Nakamoto; Cecilia M. Shikuma; Debra Ogata-Arakaki; Tracie Umaki; Edward A. Neuwelt; Bruce T. Shiramizu; Dominic C. Chow; Nisha I. Parikh; Kalpana J. Kallianpur; Bronwyn E. Hamilton (Journal of NeuroVirology, 2013)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Holocene paleoecology of a wild rice (Zizania sp.) lake in Northwestern Ontario, Canada - M. Boyd; C. Surette; J. Surette; I. Therriault; S. Hamilton (Journal of Paleolimnology, 2013)

Ecosystem respiration: Drivers of daily variability and background respiration in lakes around the globe - Christopher T. Solomon; Denise A. Bruesewitz; David C. Richardson; Kevin C. Rose; Matthew C. Van de Bogert; Paul C. Hanson; Timothy K. Kratz; Bret Larget; Rita Adrian; Brenda Leroux Babin; Chih-Yu Chiu; David P. Hamilton; et al. (Limnology and Oceanography, 2013)
We assembled data from a global network of automated lake observatories to test hypotheses regarding the drivers of ecosystem metabolism. We estimated daily rates of respiration and gross primary production (GPP) for up to a full year in each lake, via maximum likelihood fits of a free‐water metabolism model to continuous high‐frequency measurements of dissolved oxygen concentrations. Uncertainties were determined by a bootstrap analysis, allowing lake‐days with poorly constrained rate estimates to be down‐weighted in subsequent analyses. GPP and respiration varied considerably among lakes and at seasonal and daily timescales. Mean annual GPP and respiration ranged from 0.1 to 5.0 mg O 2 L −1 d −1 and were positively related to total phosphorus but not dissolved organic carbon concentration. Within lakes, significant day‐to‐day differences in respiration were common despite large uncertainties in estimated rates on some lake‐days. Daily variation in GPP explained 5% to 85% of the daily variation in respiration after temperature correction. Respiration was tightly coupled to GPP at a daily scale in oligotrophic and dystrophic lakes, and more weakly coupled in mesotrophic and eutrophic lakes. Background respiration ranged from 0.017 to 2.1 mg O 2 L −1 d −1 and was positively related to indicators of recalcitrant allochthonous and autochthonous organic matter loads, but was not clearly related to an indicator of the quality of allochthonous organic matter inputs.

Reproductive biology of squaretail coralgrouper Plectropomus areolatus using age‐based techniques - K. L. Rhodes; B. M. Taylor; C. B. Wichilmel; E. Joseph; R. J. Hamilton; G. R. Almany (Journal of Fish Biology, 2013)
The squaretail coralgrouper Plectropomus areolatus was identified as a fast‐growing, early maturing and relatively short‐lived aggregation‐spawning epinephelid. Examinations of sectioned otoliths found females and males first maturing at 2 and 3 years, respectively, suggesting protogynous hermaphroditism; however, no transitionals were observed in samples. Age distribution for the two sexes was similar and both were represented in the oldest age class; however, significant sex‐specific differences in size‐at‐age were identified. Both sexes fully recruit into the fishery at age 4 years and reach 90% of asymptotic length by age 3 years. Underwater visual assessments, combined with the gonado‐somatic indices, revealed a 5 month reproductive season, with interannual variability observed in the month of highest density within the spawning aggregation. Catch restrictions on adults during spawning times and at reproductive sites, combined with gear‐based management and enhanced enforcement, are recommended to maintain spawning stocks. Based on the available evidence, the sexual pattern for this species is unresolved.

Case studies of scenario analysis for adaptive management of natural resource and infrastructure systems - Michelle C. Hamilton; Shital A. Thekdi; Elisabeth M. Jenicek; Russell S. Harmon; Michael E. Goodsite; Michael P. Case; Christopher W. Karvetski; James H. Lambert (Environment Systems and Decisions, 2013)

Impaired Cerebellar and Limbic Responses to the Valsalva Maneuver in Heart Failure - Jennifer A. Ogren; Paul M. Macey; Rajesh Kumar; Gregg C. Fonarow; Michele A. Hamilton; Ronald M. Harper; Mary A. Woo (The Cerebellum, 2012)

The role of relatedness in structuring the social network of a wild guppy population - Darren P. Croft; P. B. Hamilton; S. K. Darden; D. M. P. Jacoby; R. James; E. M. Bettaney; C. R. Tyler (Oecologia, 2012)

A common antifungal defense strategy in Cryptocercus woodroaches and termites - M. S. Bulmer; D. Denier; J. Velenovsky; C. Hamilton (Insectes Sociaux, 2012)

Using Vegetative Nutrient Stocks to Compare Restored and Reference Wetlands in the Upper Klamath Basin, Oregon - Andrew M. Ray; Andy Hamilton; Chelsea Aquino; James C. Litts (Wetlands, 2012)

Mapping the biosphere: exploring species to understand the origin, organization and sustainability of biodiversity - Q. D. Wheeler; S. Knapp; D. W. Stevenson; J. Stevenson; S. D. Blum; B. M. Boom; G. G. Borisy; J. L. Buizer; M. R. De Carvalho; A. Cibrian; M. J. Donoghue; V. Doyle; et al. (Systematics and Biodiversity, 2012)

A community-based framework for aquatic ecosystem models - Dennis Trolle; David P. Hamilton; Matthew R. Hipsey; Karsten Bolding; Jorn Bruggeman; Wolf M. Mooij; Jan H. Janse; Anders Nielsen; Erik Jeppesen; J. Alex Elliott; Vardit Makler-Pick; Thomas Petzoldt; et al. (Hydrobiologia, 2012)

The Role of Botanic Gardens in the Science and Practice of Ecological Restoration - KATE A. HARDWICK; PEGGY FIEDLER; LYNDON C. LEE; BRUCE PAVLIK; RICHARD J. HOBBS; JAMES ARONSON; MARTIN BIDARTONDO; ERIC BLACK; DAVID COATES; MATTHEW I. DAWS; KINGSLEY DIXON; STEPHEN ELLIOTT; et al. (Conservation Biology, 2011)
Many of the skills and resources associated with botanic gardens and arboreta, including plant taxonomy, horticulture, and seed bank management, are fundamental to ecological restoration efforts, yet few of the world's botanic gardens are involved in the science or practice of restoration. Thus, we examined the potential role of botanic gardens in these emerging fields. We believe a reorientation of certain existing institutional strengths, such as plant‐based research and knowledge transfer, would enable many more botanic gardens worldwide to provide effective science‐based support to restoration efforts. We recommend botanic gardens widen research to include ecosystems as well as species, increase involvement in practical restoration projects and training practitioners, and serve as information hubs for data archiving and exchange.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

Genetic variation in strains of zebrafish (Danio rerio) and the implications for ecotoxicology studies - T. S. Coe; P. B. Hamilton; A. M. Griffiths; D. J. Hodgson; M. A. Wahab; C. R. Tyler (Ecotoxicology, 2009)

Patterns of male reproductive success in a highly promiscuous whale species: the endangered North Atlantic right whale - T. R. FRASIER; P. K. HAMILTON; M. W. BROWN; L. A. CONGER; A. R. KNOWLTON; M. K. MARX; C. K. SLAY; S. D. KRAUS; B. N. WHITE (Molecular Ecology, 2007)
Parentage analyses of baleen whales are rare, and although mating systems have been hypothesized for some species, little data on realized male reproductive success are available and the patterns of male reproductive success have remained elusive for most species. Here we combine over 20 years of photo‐identification data with high‐resolution genetic data for the majority of individual North Atlantic right whales to assess paternity in this endangered species. There was significant skew in male reproductive success compared to what would be expected if mating was random ( P 0.001). The difference was due to an excess of males assigned zero paternities, a deficiency of males assigned one paternity, and an excess of males assigned as fathers for multiple calves. The variance in male reproductive success was high relative to other aquatically mating marine mammals, but was low relative to mammals where the mating system is based on resource‐ and/or mate‐defence polygyny. These results are consistent with previous data suggesting that the right whale mating system represents one of the most intense examples of sperm competition in mammals, but that sperm competition on its own does not allow for the same degree of polygyny as systems where males can control access to resources and/or mates. The age distribution of assigned fathers was significantly biased towards older males ( P 0.05), with males not obtaining their first paternity until ~15 years of age, which is almost twice the average age of first fertilization in females (8 years), suggesting that mate competition is preventing younger males from reproducing. The uneven distribution of paternities results in a lower effective population size in this species that already has one of the lowest reported levels of genetic diversity, which may further inhibit reproductive success through mate incompatibility of genetically similar individuals.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Benthic nutrient fluxes in a eutrophic, polymictic lake - D. F. Burger; D. P. Hamilton; C. A. Pilditch; M. M. Gibbs (Hydrobiologia, 2007)

Empirical indices of spatial and executive processes in visuo-spatial working memory - J. M. Thompson; C. J. Hamilton; J. M. Gray; J. G. Quinn; P. Mackin; I. N. Ferrier; A. H. Young (Cognitive Processing, 2006)

Hinge peptide combinatorial libraries for inhilbitors of botulinum neurotoxins and saxitoxin: Deconvolution strategy - Graham J. Moore; Diana M. Moore; Samir S. Roy; Lawrence J. Hayden; Murray G. Hamilton; Nora W. C. Chan; William E. Lee (Molecular Diversity, 2006)

Unusual segregation products in sperm from a pericentric inversion 17 heterozygote - Monica M. Mikhaail-Philips; Barbara C. McGillivray; Sara J. Hamilton; Evelyn Ko; Judy Chernos; Alfred Rademaker; Renée H. Martin (Human Genetics, 2005)

The scaling of motor noise with muscle strength and motor unit number in humans - Antonia F. de C. Hamilton; Kelvin E. Jones; Daniel M. Wolpert (Experimental Brain Research, 2004)

Analysis of Anal Droplets of the Western Flower Thrips Frankliniella occidentalis - Kenneth M. MacDonald; James G. C. Hamilton; Robert Jacobson; William D. J. Kirk (Journal of Chemical Ecology, 2003)

Enumerating phytoplankton with an upright compound microscope using a modified settling chamber - P.B. Hamilton; M. Proulx; C. Earle (Hydrobiologia, 2001)

World‐wide genetic differentiation of Eubalaena : questioning the number of right whale species - H. C. Rosenbaum; R. L. Brownell; M. W. Brown; C. Schaeff; V. Portway; B. N. White; S. Malik; L. A. Pastene; N. J. Patenaude; C. S. Baker; M. Goto; P. B. Best; et al. (Molecular Ecology, 2000)
Few studies have examined systematic relationships of right whales ( Eubalaena spp.) since the original species descriptions, even though they are one of the most endangered large whales. Little morphological evidence exists to support the current species designations for Eubalaena glacialis in the northern hemisphere and E. australis in the southern hemisphere. Differences in migratory behaviour or antitropical distribution between right whales in each hemisphere are considered a barrier to gene flow and maintain the current species distinctions and geographical populations. However, these distinctions between populations have remained controversial and no study has included an analysis of all right whales from the three major ocean basins. To address issues of genetic differentiation and relationships among right whales, we have compiled a database of mitochondrial DNA control region sequences from right whales representing populations in all three ocean basins that consist of: western North Atlantic E. glacialis , multiple geographically distributed populations of E. australis and the first molecular analysis of historical and recent samples of E. glacialis from the western and eastern North Pacific Ocean. Diagnostic characters, as well as phylogenetic and phylogeographic analyses, support the possibility that three distinct maternal lineages exist in right whales, with North Pacific E. glacialis being more closely related to E. australis than to North Atlantic E. glacialis . Our genetic results provide unequivocal character support for the two usually recognized species and a third distinct genetic lineage in the North Pacific under the Phylogenetic Species Concept, as well as levels of genetic diversity among right whales world‐wide.

Pollen‐based biome reconstruction for southern Europe and Africa 18,000 yr bp - H. Elenga; O. Peyron; R. Bonnefille; D. Jolly; R. Cheddadi; J. Guiot; V. Andrieu; S. Bottema; G. Buchet; J.‐L. De Beaulieu; A. C. Hamilton; J. Maley; et al. (Journal of Biogeography, 2000)
Pollen data from 18,000 14 C yr bp were compiled in order to reconstruct biome distributions at the last glacial maximum in southern Europe and Africa. Biome reconstructions were made using the objective biomization method applied to pollen counts using a complete list of dryland taxa wherever possible. Consistent and major differences from present‐day biomes are shown. Forest and xerophytic woods/scrub were replaced by steppe, both in the Mediterranean region and in southern Africa, except in south‐western Cape Province where fynbos (xerophytic scrub) persisted. Sites in the tropical highlands, characterized today by evergreen forest, were dominated by steppe and/or xerophytic vegetation (cf. today’s Ericaceous belt and Afroalpine grassland) at the last glacial maximum. Available data from the tropical lowlands are sparse but suggest that the modern tropical rain forest was largely replaced by tropical seasonal forest while the modern seasonal or dry forests were encroached on by savanna or steppe. Montane forest elements descended to lower elevations than today.

Minor Constituent Concentrations Measured from a High Altitude Aircraft Using High Resolution Far-Infrared Fourier Transform Spectroscopy - B. Carli; P. Ade; M. Carlotti; U. Cortesi; A. Gignoli; P. Hamilton; M. Lanfranchi; C. Lee; A. R. MacKenzie; A. Phillips (Journal of Atmospheric Chemistry, 2000)

Expressed sequence tags derived from brain tissue of Oreochromis niloticus - L. C. Hamilton; G. R. Macpherson; J. M. Wright (Journal of Fish Biology, 2000)
Expressed sequence tags (ESTs) were obtained from complementary DNA libraries derived from the brain of the cichlid fish, Oreochromis niloticus. Single‐pass sequencing of 183 cDNA clones generated 294 ESTs; 57 of these clones (31%) were identified based on their similarity to sequences in GenBank.

Microsatellites from the Amazonian tree Dinizia excelsa (Fabaceae) - C. W. Dick; M. B. Hamilton (Molecular Ecology, 1999)

GENETIC BASIS AND EVOLUTIONARY SIGNIFICANCE OF VENTRAL SKIN COLOR MARKINGS IN NORTH ATLANTIC RIGHT WHALES ( EUBALAENA GLACIALIS ) - C. M. Schaeff; P. K. Hamilton (Marine Mammal Science, 1999)
A bstract Approximately one third of the North Atlantic right whale population has white ventral skin patches. Most white‐marked animals have both a belly and a chin patch, and the distribution of white pigment suggests that the patches represent a single ventral marking that varies in size and location. Population frequencies and cow‐calf inheritance patterns indicate that the white mark is an autosomal recessive trait. There is no evidence to suggest that ventral coloration patterns are currently under selection. White‐marked and black cows appear to experience similar levels of reproductive success based on calving intervals and length of sighting histories. Also, white‐marked animals were equally common among cows and nulliparous adult females and among live vs . dead animals. Male reproductive success could not be tested because calf paternity is not known; white‐marked and black males exhibit similar survival rates. White‐marked cows were more common among females that took some or all of their calves to the Bay of Fundy summer nursery area compared to females that did not visit Fundy. This suggests that female habitat‐use patterns may influence nuclear gene flow. Increased sample sizes and additional markers are needed to further investigate gene flow.

Improved diagnosis of cowpea aphid-borne mosaic virus in Africa: significance for cowpea seed-indexing, breeding programs and potyvirus taxonomy - C. Huguenot; M. T. Furneaux; J. A. Clare; R. I. Hamilton (Archives of Virology, 1996)

High level production of potyvirus-like particles in insect cells infected with recombinant baculovirus - S. J. Edwards; M. B. Hayden; R. C. Hamilton; J. A. Haynes; I. T. Nisbet; M. N. Jagadish (Archives of Virology, 1994)